Kemampuan Bertanggung Jawab Orang yang Mempunyai Gangguan Jiwa Akibat Melakukan Tindak Pidana Narkotika - Fahmi Ramadhan; H.R. Adianto Mardijono (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2023)
The purpose of this research was to find out the criminal responsibility of narcotics offenders who have mental disorders. The research carried out is normative law research where secondary information is obtained by conducting bibliographical studies. The process of changing the data is then carried out in a qualitative way. The case discussed is a narcotics crime, but it was committed by a person with mental disorders within the jurisdiction of the Sumenep District Court as proven by a psychiatrist as an expert witness who works at the RSUD. Dr. H. Moh Anwar, Sumenep. In this case, which showed that the defendant with proof of a letter issued by a psychiatrist stated that the person concerned had mental and behavioral disorders due to drug addiction and residual schizophrenia, the judge did not convict or acquit the defendant for the crime of class I narcotics but ordered him to go to the Menur Mental Hospital in Surabaya or Dr. Radjiman Wediodiningrat Mental Hospital in Lawang to carry out maintenance actions. Based on that, a person who has a mental disorder commits a narcotic crime, is subject to the provisions of legal regulations in Indonesia, namely that he cannot be convicted or acquitted of all charges.